Application of Soft Robots in Rehabilitation Training - Wang Chengjun; Deng Hailong (Jixie chuandong)
Aiming at the problems of poor adaptability, low flexibility and inconvenient operation and carrying of traditional rigid robots, the application prospect of the soft robot in the field of rehabilitation training is introduced. Firstly, according to the source of soft robots, the key technologies such as materials, driving technology, sensing and control are introduced and analyzed. Secondly, the current research and application status of soft robots in rehabilitation training tasks in different parts of the human body are summarized. Thirdly, the problems faced by soft robots in rehabilitation training are introduced from the aspects of materials, structure and control. Finally, the future development and application of rehabilitation training in soft robots are prospected to provide reference for the follow-up study of rehabilitation training in soft robots.